Neutropenic enterocolitis - Fabio G Rodrigues; Gil Valdo José da Silva; Steven D. Wexner (2017)
Neutropenic colitis is a severe condition usually affecting immunocompromised patients.Its exact pathogenesis is not completely understood.The main elements in disease onset appear to be intestinal mucosal injury together with neutropenia and the weakened immune system of the afflicted patients.These initial conditions lead to intestinal edema, engorged vessels, and a disrupted mucosal surface, which becomes more vulnerable to bacterial intramural invasion.Chemotherapeutic agents can cause direct mucosal injury (mucositis) or can predispose to distension and necrosis, thereby altering intestinal motility.This article aims to review current concepts regarding neutropenic colitis' pathogenesis, diagnosis, and management.